2013
DOI: 10.1016/j.psychres.2013.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Association between attachment prototypes and schizotypy dimensions in two independent non-clinical samples of Spanish and American young adults

Abstract: Attachment theory offers a powerful theoretical framework for elucidating the developmental pathway through which childhood interpersonal trauma confers vulnerability to psychosis. In the present study, the association between attachment and schizotypy was explored in two independent non-clinical samples of Spanish (n=547) and American (n=1425) young adults. Participants completed the Relationship Questionnaire and the Wisconsin Schizotypy Scales. Following attachment theory and cognitive accounts of psychosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 51 publications
(61 reference statements)
0
18
0
6
Order By: Relevance
“…Positive schizotypy has been associated with both attachment avoidance (Berry et al, 2007a; MacBeth et al, 2008) and attachment anxiety (Berry et al, 2007a), while negative schizotypal symptoms have been specifically linked to attachment avoidance (Berry et al, 2006, 2007a; Tiliopoulos and Goodall, 2009). In a large community study, preoccupied attachment was associated to positive schizotypy, dismissing attachment was related to negative schizotypy and fearful attachment was related to both positive and negative schizotypy (Sheinbaum et al, 2013). Given that preoccupied attachment is characterized by hyper-activation of the attachment system (Shaver and Mikulincer, 2002), these findings support the possibility that disruptions in the regulation of negative emotion, and increased salience of threat-related cues and distress may contribute to the expression and maintenance of positive schizotypy.…”
Section: Trauma Attachment and Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…Positive schizotypy has been associated with both attachment avoidance (Berry et al, 2007a; MacBeth et al, 2008) and attachment anxiety (Berry et al, 2007a), while negative schizotypal symptoms have been specifically linked to attachment avoidance (Berry et al, 2006, 2007a; Tiliopoulos and Goodall, 2009). In a large community study, preoccupied attachment was associated to positive schizotypy, dismissing attachment was related to negative schizotypy and fearful attachment was related to both positive and negative schizotypy (Sheinbaum et al, 2013). Given that preoccupied attachment is characterized by hyper-activation of the attachment system (Shaver and Mikulincer, 2002), these findings support the possibility that disruptions in the regulation of negative emotion, and increased salience of threat-related cues and distress may contribute to the expression and maintenance of positive schizotypy.…”
Section: Trauma Attachment and Psychosismentioning
confidence: 99%
“…On the other hand, dismissing attachment, characterized by a deactivation of the attachment system (i.e., interpersonal distancing, etc. ), is significantly associated with negative schizotypy (Sheinbaum et al, 2013), which may contribute to persistent social withdrawal and isolation. In a recent study with a large sample of undergraduate students, fearful attachment was found to mediate the relationship between physical/emotional trauma and both positive and negative schizotypy (Sheinbaum et al, 2014).…”
Section: Trauma Attachment and Psychosismentioning
confidence: 99%
“…In particular, avoidant attachment has been associated with positive and negative symptoms in persons with schizophrenia (Ponizovsky et al, 2007), as well as paranoia in both psychotic patients and individuals with early psychosis (Berry et al, 2008a;Korver-Nieberg et al, 2013). In addition, the preoccupied and fearful attachment styles have been associated with higher levels of positive symptoms in patients with schizophrenia (Ponizovsky et al, 2013) and with positive schizotypy in nonclinical samples (Sheinbaum et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…These patterns could mediate the use of dysfunctional cognitive mechanisms and affective dysregulation, which, probably in interaction, might lead to reality distortion (Read et al, 2009). Also, the characteristics associated with the chronic deactivation of the attachment system, such as interpersonal disengagement and minimization of emotional expression (Mikulincer and Shaver, 2007), might contribute to the ontogeny of negative symptoms (Sheinbaum et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…The Chapman psychosis-proneness scales, which were developed in the late 1970s and early 1980s [24], are a series of scales that were designed to assess schizotypy tendencies in psychiatrically normal people [19,[25][26][27]. Four of the scales in this series, namely the Perceptual Aberration Scale, Magical Ideation Scale, Physical Anhedonia Scale, and Social Anhedonia Scale, form a schizotypy assessment battery known as the Wisconsin schizotypy scales (WSS).…”
mentioning
confidence: 99%